Managerial Leadership Qualities in the Financial Institutions of Nepal - Shrestha, Prakash (Pravaha, 2020)
Leadership and leaders matters effectively and confidently effect on outcomes ofthe organization. Certain leadership characteristics and qualities are important to improve leadership effectiveness and organizational performance. This study is based on two major qualities of leadership such as relationship-oriented and task-oriented. Developing others, supporting team, identifying the pain and interpersonal skills were taken as dependent variables of relationship-oriented qualities. Likewise, developing self, business acumen, commitment, pursuit of excellence and accountability/focus were taken as dependent variables of task oriented qualities. It was concerned with the managerial qualities of managers working in financial institutions of Nepal (including three commercial banks, three development banks, three finance companies, and three insurance companies). In total 60 managers (5 of each organization) and 120 (10 of each organization) were the respondents. Their opinions were used for analysis purposes in this study. The Likert-scale questionnaire was used as the tool for data collection. It was composed of five points showing 5 represents strongly agree to 1 indicates strongly disagree. The empirical results of this study indicated that on the basis of relationship-oriented, "identifying the pain" was the most desirable quality of leaders (managers) by employees whereas on the basis of task-oriented, “pursuit of excellence" was the most desirable quality of leaders (managers) from employee perspective of the financial institutions of Nepal. Based on managers ‘perspective, the most desirable quality of leaders was "interpersonal skills" in terms of relationship-oriented leadership qualities, whereas in terms of task oriented qualities, the most desirable quality of leaders by the manager was" commitment". The leadership qualities are best while targeting to accomplish the organizational task on time.